Synthesis method of rare earth-benzotriazole composite ultraviolet absorption material and application of rare earth-benzotriazole composite ultraviolet absorption material in anti-aging fibers

Through the synthesis of rare earth-benzotriazole composite materials and the preparation of anti-aging fibers, the problem of insufficient performance of ultraviolet absorbing materials in the UVA and UVB bands in the prior art is solved, and the good anti-aging performance of fibers in the entire ultraviolet band is achieved. The balance between mechanical properties has wide application prospects.

CN119219871AInactive Publication Date: 2024-12-31TIANJIN BAOGANG RES INST OF RARE EARTHS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411774993.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing ultraviolet absorbing materials have insufficient performance in the UVA and UVB bands, especially inorganic shielding agents have poor performance in the UVA band, while organic shielding agents have weak absorption capacity in the UVB band and cannot effectively protect the fibers from ultraviolet aging.

Method used

The synthesis method of rare earth-benzotriazole composite ultraviolet absorbing materials is adopted, and the pH value and temperature are adjusted by reacting octyl triazole, isobutylamine, phenol compounds and polyacetals under a nitrogen atmosphere, and rare earth oxides are added to adjust the pH value and temperature. Materials with excellent UV absorption capacity were prepared, and extruded and spinned with PET slices to prepare anti-aging fibers.

Benefits of technology

The material exhibits excellent absorption capacity in the entire UV band, improving the fiber's UV resistance and anti-aging properties, while maintaining mechanical properties, and providing good anti-oxidant capacity without the need for additional antioxidants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219871A_ABST
    Figure CN119219871A_ABST
Patent Text Reader

Abstract

The invention provides a synthesis method of a rare earth-benzotriazole composite ultraviolet absorption material and application of the rare earth-benzotriazole composite ultraviolet absorption material in anti-aging fibers, and the synthesis method comprises the following steps: putting octyl phenol triazole, isobutylamine, p-methoxyphenol and polyacetal into a solvent, and reacting for 4-6 hours at 150-180 DEG C in a nitrogen atmosphere to obtain the rare earth-benzotriazole composite ultraviolet absorption material. Adding sodium hydroxide after the reaction is completed, then cooling to 100-120 DEG C, then reacting for 2-4 hours, cooling to 80 DEG C after the reaction is completed, adding rare earth oxide, adjusting the pH value of the solution to be 10, heating to 120-160 DEG C in a nitrogen atmosphere, reacting for 12-18 hours, and then centrifuging, washing, drying and crushing to obtain the rare earth-rare earth composite material. The rare earth-benzotriazole composite ultraviolet absorption material is obtained. According to the rare earth-benzotriazole composite ultraviolet absorption material disclosed by the invention, octylphenol triazole and p-methoxyphenol are combined, so that good high thermal stability can be provided, and the rare earth-benzotriazole composite ultraviolet absorption material cannot be decomposed due to high temperature in a granulation spinning process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of textiles, and in particular relates to a synthesis method of a rare earth-benzotriazole composite ultraviolet absorption material and application of the material in anti-aging fibers. Background Art

[0002] Ultraviolet light is an invisible electromagnetic wave with a shorter wavelength than visible light. The ultraviolet spectrum accounts for about 6% of sunlight. Ultraviolet rays of different wavelengths can be divided into UVA, UVB and UVC. An appropriate amount of ultraviolet radiation can promote the synthesis of vitamin D in the body, inhibit rickets, disinfect and sterilize, and is beneficial to the human body, but excessive ultraviolet radiation is extremely harmful to the human body. UVA has a relatively small energy, accounting for 95-98% of ultraviolet rays, which can make the skin loose and accelerate aging; UVB has a large energy, which can cause sunburn, immunosuppression, and increase the risk of skin tumors and cancer; UVC has the highest energy, which can cause gene mutations and tumors, but is almost completely absorbed by the ozone layer.

[0003] UV absorbing materials mainly include inorganic shielding agents and organic shielding agents according to their chemical composition. Inorganic shielding agents mainly refract, reflect and scatter incident ultraviolet rays. They usually have a large refractive index and a large reflectivity. In addition, if the incident ultraviolet rays are near the absorption band of the selected shielding material, the refractive index will increase significantly, and the reflectivity will also increase. However, inorganic materials are limited by the influence of their own crystal lattices, resulting in their performance in the UVA band not being very good. Organic shielding agents are mostly aromatic derivatives containing chromophores and auxochromes, which can undergo photophysical and photochemical effects, and can strongly and selectively absorb high-energy ultraviolet rays, and convert them into other harmless forms of energy for release. The action process is that the shielding agent absorbs ultraviolet energy to produce electron migration, and the ground state is excited to the lowest excited or higher excited singlet state, and then may return to the ground state in the form of emitting fluorescence, but the absorption performance in the UVB band is not as good as that of inorganic shielding agents. Summary of the invention

[0004] In view of this, the present invention aims to overcome the defects in the prior art and proposes a synthesis method of a rare earth-benzotriazole composite ultraviolet absorption material and its application in anti-aging fibers.

[0005] To achieve the above object, the technical solution of the present invention is achieved as follows: A method for synthesizing a rare earth-benzotriazole composite ultraviolet absorbing material comprises the following steps: Put octanotriazole, isobutylamine, phenolic compounds and polyacetal into a solvent, react for 4-6 hours under a nitrogen atmosphere at 150-180° C., add sodium hydroxide after the reaction, cool to 100-120° C. and react for 2-4 hours, cool to 70-80° C. after the reaction, add rare earth oxide, adjust the pH value of the solution to 9-10, heat to 120-160° C. under a nitrogen atmosphere and react for 12-18 hours, then centrifuge, wash, dry and crush to obtain the rare earth-benzotriazole composite ultraviolet absorption material.

[0006] Furthermore, the molar ratio of octanotriazole, isobutylamine, phenolic compound, polyacetal and sodium hydroxide is 1:0.5-1:1-1.4:0.6-1:0.1-0.4; and the phenolic compound is p-methoxyphenol and / or m-methoxyphenol.

[0007] Furthermore, the molar ratio of octylphenoltriazole to rare earth oxide is 4-18:1-3.

[0008] Furthermore, the amount of the solvent added is: 300-400 mL of solvent per mole of octylphenoltriazole; and the solvent is at least one of toluene, ether or acetone.

[0009] Furthermore, the rare earth oxide is cerium oxide and / or cerium lanthanum oxide.

[0010] A rare earth-benzotriazole composite ultraviolet absorption material prepared by the preparation method.

[0011] The rare earth-benzotriazole composite ultraviolet absorption material is used in the preparation of anti-aging fibers, and the anti-aging fibers are anti-aging polyester fibers.

[0012] Furthermore, the anti-aging polyester fiber is made by the following steps: extruding the rare earth-benzotriazole composite ultraviolet absorption material and PET slices to obtain an anti-aging polyester masterbatch, and spinning, drawing and winding the anti-aging polyester masterbatch and PET masterbatch to obtain the anti-aging polyester fiber.

[0013] Furthermore, the mass ratio of the rare earth-benzotriazole composite ultraviolet absorption material to the PET slice is 2-3:7-8; the mass ratio of the anti-aging polyester masterbatch to the PET masterbatch is 3-12:88-97.

[0014] Furthermore, the PET slices are high-viscosity PET slices; and the PET masterbatch is high-viscosity PET masterbatch.

[0015] Compared with the prior art, the present invention has the following advantages: The presence of phenolic hydroxyl groups in the phenolic compounds and octylphenoltriazole in the rare earth-benzotriazole composite ultraviolet absorption material of the present invention can make the hydrogen atoms on the benzene ring more easily replaced. The two materials are combined in a single chain form, so that the thermal stability of the material is improved and decomposition will not occur due to high temperature during the granulation and spinning process. At the same time, p-methoxyphenol can play an inhibitory effect to improve the uniformity of material distribution, and has good compatibility with the polymer matrix. On the premise of significantly improving ultraviolet protection and anti-aging, it has little effect on the mechanical properties of the fiber.

[0016] After the octinoxate triazole and para-oxymethylphenol in the rare earth-benzotriazole composite ultraviolet absorption material of the present invention are combined with rare earth ions, the strong absorption effect of the rare earth metal ions on the UVB band can make up for the defect of weak ultraviolet absorption ability of organic materials in the UVB band, so that the composite material can have excellent ultraviolet absorption ability in the entire ultraviolet band.

[0017] The valence state of cerium in the naturally distributed lanthanum-cerium rare earth oxide in the rare earth-benzotriazole composite ultraviolet absorption material of the present invention is a complex of +3 and +4, which can combine with oxygen free radicals to provide good antioxidant capacity without the need to introduce other antioxidants. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a Fourier transform infrared spectrum of the rare earth-benzotriazole composite ultraviolet absorption material described in Example 1 of the present invention; Figure 2 This is an electron microscope image of the rare earth-benzotriazole composite ultraviolet absorption material described in Example 1 of the present invention; Figure 3 This is an electron micrograph of a cross section of the anti-aging polyester masterbatch described in Example 1 of the present invention. DETAILED DESCRIPTION

[0019] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0020] The present invention will be described in detail below with reference to the embodiments.

[0021] Example 1

[0022] A method for preparing anti-aging polyester fiber comprises the following steps: (1) In a reactor equipped with a condensing device, 6 mol of octyl triazole, 4.8 mol of isobutylamine, 6 mol of p-methoxyphenol, 3.6 mol of polyacetal and 2000 ml of toluene were placed, and the temperature was raised to 160°C for reaction for 4 hours under a nitrogen atmosphere. Then, 1.8 mol of sodium hydroxide was added, and the temperature was lowered to 120°C for reaction for 2 hours. After 2 hours, the temperature was lowered to 80°C. 3 mol of lanthanum cerium oxide was added to the reactor, and the pH value was adjusted to 10 with ammonia water. The reactor was heated to 120°C for reaction for 12 hours under a nitrogen atmosphere. After the reaction was completed, the temperature was naturally lowered and cooled. Then, the reactor was washed with ethanol and centrifuged. The reaction was repeated 3 times. The reactor was dried at 80°C for 10 hours in a vacuum oven. Finally, the rare earth-benzotriazole composite ultraviolet absorption material was obtained by grinding and crushing. The infrared spectrum was as follows: Figure 1 As shown in the electron microscope image Figure 2 As shown; (2) 3 kg of rare earth-benzotriazole composite ultraviolet absorption material was mixed with 7 kg of high-viscosity PET slices. After dehumidification and drying, the mixed materials were injected into a screw extruder for blending to obtain anti-aging polyester masterbatch. The cross-sectional electron microscopy image is shown in the figure. Figure 3 As shown; 10 kg of anti-aging polyester masterbatch and 90 kg of high-viscosity PET polyester chips are put into a melt spinning machine for spinning. The spinning temperature is 280°C, and the filament bundles are evenly ejected from the spinneret. After side blowing cooling, they are wound into shape after heat setting. The winding speed is 2970 m / min, and the anti-aging fibers are collected. The collected anti-aging fibers are divided into warp yarns and weft yarns, and plain fabrics with a width of 1 m and a length of 4 m are woven on a loom to obtain anti-aging fabric A.

[0023] Example 2

[0024] A method for preparing anti-aging polyester fiber comprises the following steps: (1) 6 mol of octanotriazole, 5.4 mol of isobutylamine, 7.2 mol of p-methoxyphenol, 4.2 mol of polyacetal and 2400 ml of toluene were placed in a reactor equipped with a condensing device, and the temperature was raised to 180°C for reaction for 6 hours under a nitrogen atmosphere, and then 2.4 mol of sodium hydroxide was added, and the temperature was lowered to 120°C for reaction for 3 hours. After 3 hours, the temperature was lowered to 80°C, and 2 mol of cerium oxide was added to the reactor. The pH value was adjusted to 10 with ammonia water, and the reaction was heated to 120°C for reaction for 12 hours under a nitrogen atmosphere. After the reaction was completed, the temperature was naturally lowered and cooled, and then washed and centrifuged with ethanol, and the reaction was repeated 3 times. The rare earth-benzotriazole composite ultraviolet absorption material was finally ground and crushed to obtain; (2) 3 kg of rare earth-benzotriazole composite ultraviolet absorption material was mixed with 7 kg of high-viscosity PET chips. After the mixed material was dehumidified and dried, it was injected into a screw extruder for blending to obtain an anti-aging polyester masterbatch; 10 kg of the anti-aging polyester masterbatch and 90 kg of the high-viscosity PET polyester chips were put into a melt spinning machine for spinning at a spinning temperature of 280 ° C. The filament bundles were evenly ejected from the spinneret, cooled by side blowing, and wound into shape after heat setting at a winding speed of 2970 m / min. The anti-aging fibers were collected and divided into warp yarns and weft yarns. A plain fabric with a width of 1 m and a length of 4 m was woven on a loom to obtain an anti-aging fabric B.

[0025] Comparative Example 1 A method for preparing an anti-aging polyester fiber comprises the following steps: injecting 10 kg of high-viscosity PET chips into a screw extruder after dehumidification and drying, and blending them to obtain an anti-aging polyester masterbatch; taking 10 kg of the anti-aging polyester masterbatch and 90 kg of high-viscosity PET polyester chips and putting them into a melt spinning machine for spinning at a spinning temperature of 280°C, allowing the filament bundle to be uniformly ejected from the spinneret, cooling by side blowing, and winding after heat setting at a winding speed of 2970 m / min, collecting the anti-aging fibers, dividing the collected anti-aging fibers into warp yarns and weft yarns, and weaving a plain fabric with a width of 1 m and a length of 4 m on a loom to obtain the anti-aging fabric C.

[0026] Comparative Example 2 A method for preparing an anti-aging polyester fiber comprises the following steps: mixing 3kg of lanthanum cerium oxide with 7kg of high-viscosity PET chips, dehumidifying and drying the mixed materials, injecting the mixed materials into a screw extruder for blending to obtain an anti-aging polyester masterbatch; taking 10kg of the anti-aging polyester masterbatch and 90kg of the high-viscosity PET polyester chips and putting them into a melt spinning machine for spinning at a spinning temperature of 280°C, allowing the filament bundle to be uniformly ejected from the spinneret, cooling by side blowing, and winding after heat setting at a winding speed of 2970m / min, collecting the anti-aging fibers, dividing the collected anti-aging fibers into warp yarns and weft yarns, and weaving a plain fabric with a width of 1m and a length of 4m on a loom to obtain an anti-aging fabric D.

[0027] Comparative Example 3 A method for preparing anti-aging polyester fiber comprises the following steps: (1) In a reaction kettle equipped with a condensing device, 6 mol of octyl triazole, 4.8 mol of isobutylamine, 6 mol of p-methoxyphenol, 3.6 mol of polyacetal and 2000 ml of toluene were placed, and the temperature was raised to 160° C. for reaction for 4 hours under a nitrogen atmosphere, and then 1.8 mol of sodium hydroxide was added, and the temperature was lowered to 120° C. for reaction for 2 hours. After 2 hours, the mixture was cooled to room temperature, washed with ethanol and centrifuged, and the mixture was repeated 3 times. The mixture was dried in a vacuum oven at 80° C. for 10 hours, and finally ground to obtain a benzotriazole composite ultraviolet absorption material; (2) 3 kg of benzotriazole composite ultraviolet absorption material was mixed with 7 kg of high-viscosity PET chips. After the mixed material was dehumidified and dried, it was injected into a screw extruder for blending to obtain an anti-aging polyester masterbatch; 10 kg of the anti-aging polyester masterbatch and 90 kg of the high-viscosity PET polyester chips were put into a melt spinning machine for spinning at a spinning temperature of 280 ° C. The filament bundles were evenly ejected from the spinneret, cooled by side blowing, and wound into shape after heat setting at a winding speed of 2970 m / min. The anti-aging fibers were collected and divided into warp yarns and weft yarns. A plain fabric with a width of 1 m and a length of 4 m was woven on a loom to obtain the anti-aging fabric E.

[0028] Comparative Example 4 A method for preparing anti-aging polyester fiber comprises the following steps: (1) 6 mol of octanotriazole, 4.8 mol of isobutylamine, 6 mol of o-methoxyphenol, 3.6 mol of polyacetal and 2000 ml of toluene were placed in a reactor equipped with a condensing device, and the temperature was raised to 160° C. for reaction for 4 hours under a nitrogen atmosphere, and then 1.8 mol of sodium hydroxide was added, and the temperature was lowered to 120° C. for reaction for 2 hours, and then the temperature was lowered to 80° C. after 2 hours, and 3 mol of lanthanum cerium oxide was added to the reactor, and the pH value was adjusted to 10 with ammonia water, and the reaction was heated to 120° C. for reaction for 12 hours under a nitrogen atmosphere. After the reaction was completed, the temperature was naturally lowered and cooled, and then washed and centrifuged with ethanol, and the reaction was repeated 3 times, and dried in a vacuum oven at 80° C. for 10 hours, and finally ground to obtain a rare earth-benzotriazole composite ultraviolet absorption material; (2) 3 kg of rare earth-benzotriazole composite ultraviolet absorption material was mixed with 7 kg of high-viscosity PET chips. After the mixed material was dehumidified and dried, it was injected into a screw extruder for blending to obtain an anti-aging polyester masterbatch; 10 kg of the anti-aging polyester masterbatch and 90 kg of the high-viscosity PET polyester chips were put into a melt spinning machine for spinning at a spinning temperature of 280 ° C. The filament bundle was evenly ejected from the spinneret, cooled by side blowing, and wound into shape after heat setting at a winding speed of 2970 m / min. The anti-aging fibers were collected and divided into warp yarns and weft yarns. A plain fabric with a width of 1 m and a length of 4 m was woven on a loom to obtain an anti-aging fabric F.

[0029] Comparative Example 5 A method for preparing anti-aging polyester fiber comprises the following steps: (1) In a reaction kettle equipped with a condensing device, 6 mol of octanotriazole, 4.8 mol of isobutylamine, 6 mol of p-methoxyphenol, 3.6 mol of polyacetal, 3 mol of cerium lanthanum oxide and 2000 ml of toluene were placed, the temperature was raised to 100° C. for reaction for 4 hours under a nitrogen atmosphere, and then 1.8 mol of sodium hydroxide was added, the temperature was lowered to continue to react at 100° C. for 2 hours, and the temperature was naturally lowered after the reaction was completed. Then, the mixture was washed with ethanol and centrifuged, and the process was repeated 3 times. The mixture was dried in a vacuum oven at 80° C. for 10 hours, and finally ground to obtain a rare earth-benzotriazole composite ultraviolet absorption material; (2) 3 kg of rare earth-benzotriazole composite ultraviolet absorption material was mixed with 7 kg of high-viscosity PET chips. After the mixed material was dehumidified and dried, it was injected into a screw extruder for blending to obtain an anti-aging polyester masterbatch; 10 kg of the anti-aging polyester masterbatch and 90 kg of the high-viscosity PET polyester chips were put into a melt spinning machine for spinning at a spinning temperature of 280 ° C. The filament bundles were evenly ejected from the spinneret, cooled by side blowing, and wound into shape after heat setting at a winding speed of 2970 m / min. The anti-aging fibers were collected and divided into warp yarns and weft yarns. A plain fabric with a width of 1 m and a length of 4 m was woven on a loom to obtain the anti-aging fabric G.

[0030] The physical properties of the anti-aging fabrics prepared in Examples 1-2 of the present invention and Comparative Examples 1-5, including mechanical properties and anti-ultraviolet properties, were measured respectively. The results are shown in Table 1.

[0031] Table 1 Performance results

[0032] As can be seen from Table 1, the UPF of Examples 1-2 is all above 170, far exceeding 50, and has excellent anti-ultraviolet ability. It can be seen from Comparative Example 1 that the addition of composite materials does not reduce the mechanical properties of fabrics too much. It can be seen from Comparative Examples 2-3 that the two materials each show good performance in UVA and UVB, but do not fully reach the level of national standards in the entire band, and Examples 1-2 combine the advantages of both, and further improve the advantages, so that the fabric has good anti-ultraviolet performance in the full ultraviolet band. Comparative Example 4 replaces phenolic compounds of different structures, because its ortho-position structure stability is weak, it is easy to decompose and agglomerate during the synthesis process and high-temperature spinning process, causing the fabric strength and performance to decline. Comparative Example 5 adds all reactants to the container during the initial synthesis process and maintains a constant temperature reaction, and octylphenol triazole and methoxyphenol cannot be fully combined.

[0033] The samples of the above Examples 1-2 and Comparative Examples 1-5 were placed in an aging box for 360 hours of aging test, and their mechanical properties and anti-ultraviolet properties were tested again after being taken out.

[0034] Table 2 Performance results

[0035] Five samples were subjected to UV accelerated aging tests. From Table 2, it can be seen that the mechanical properties of Examples 1-2 did not change significantly, and the UV resistance still met the national standard. On the contrary, the mechanical properties and UV resistance of Comparative Examples 1-5 showed a significant downward trend.

[0036] In summary, the application of the rare earth-benzotriazole composite ultraviolet absorption material and synthetic machine in anti-aging fibers of the present invention not only has obvious advantages in anti-ultraviolet performance, but also has good antioxidant ability, and does not have excessive impact on the mechanical properties of the fibers, and has broad application prospects.

[0037] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for synthesizing a rare earth-benzotriazole composite ultraviolet absorbing material, characterized in that: The steps include: Put octanotriazole, isobutylamine, phenolic compounds and polyacetal into a solvent, react for 4-6 hours under a nitrogen atmosphere at 150-180° C., add sodium hydroxide after the reaction, cool to 100-120° C. and react for 2-4 hours, cool to 70-80° C. after the reaction, add rare earth oxide, adjust the pH value of the solution to 9-10, heat to 120-160° C. under a nitrogen atmosphere and react for 12-18 hours, then centrifuge, wash, dry and crush to obtain the rare earth-benzotriazole composite ultraviolet absorption material.

2. The method for synthesizing the rare earth-benzotriazole composite ultraviolet absorbing material according to claim 1, characterized in that: The molar ratio of octanotriazole, isobutylamine, phenolic compound, polyacetal and sodium hydroxide is 1:0.5-1:1-1.4:0.6-1:0.1-0.4; the phenolic compound is p-methoxyphenol and / or m-methoxyphenol.

3. The method for synthesizing the rare earth-benzotriazole composite ultraviolet absorbing material according to claim 1, characterized in that: The molar ratio of octylphenol triazole to rare earth oxide is 4-18:1-3.

4. The method for synthesizing the rare earth-benzotriazole composite ultraviolet absorbing material according to claim 1, characterized in that: The added amount of the solvent is: 300-400 mL of solvent is added per mole of octylphenoltriazole; the solvent is at least one of toluene, ether or acetone.

5. The method for synthesizing the rare earth-benzotriazole composite ultraviolet absorbing material according to claim 1, characterized in that: The rare earth oxide is cerium oxide and / or cerium lanthanum oxide.

6. A rare earth-benzotriazole composite ultraviolet absorption material prepared by the synthesis method according to any one of claims 1 to 5.

7. The use of the rare earth-benzotriazole composite ultraviolet absorption material according to claim 6 in the preparation of anti-aging fibers, characterized in that: The anti-aging fiber is anti-aging polyester fiber.

8. The use according to claim 7, characterized in that: The anti-aging polyester fiber is made by the following steps: extruding the rare earth-benzotriazole composite ultraviolet absorption material and PET slices to obtain anti-aging polyester masterbatch, and spinning, drawing and winding the anti-aging polyester masterbatch and PET masterbatch to obtain the anti-aging polyester fiber.

9. The use according to claim 8, characterized in that: The mass ratio of the rare earth-benzotriazole composite ultraviolet absorption material to the PET slice is 2-3:7-8; the mass ratio of the anti-aging polyester masterbatch to the PET masterbatch is 3-12:88-97.

10. The use according to claim 8, characterized in that: The PET slices are high-viscosity PET slices; and the PET masterbatch is high-viscosity PET masterbatch.

Citation Information

Patent Citations

  • Substituted benzotriazole phenols

    CN108026054A

  • Rare earth-added anti-ultraviolet anti-aging synthetic fiber as well as preparation method and application thereof

    CN112899801A

  • Rare earth-added anti-ultraviolet anti-aging viscose fiber and preparation method thereof

    CN113005551A

  • Sunscreen or daily care composition comprising bis-ethylhexyloxyphenol methoxyphenyl triazine and inorganic uv filter

    CN118019517A

  • Triazole co-condensed material and method for producing the same

    JP2010037501A